Design of a Controller for Voltage Regulation in a Hybrid UAV (LACCEI, 2024)
We propose a power control system for a UAV based on a bidirectional Buck-Boost converter. The control technology proposed switching a MOSFET to regulate the current by employing an internal PI control and external control to regulate the DC bus voltage. In addition, we proposed and integrated a unidirectional Boost system to regulate the output voltage (Vo). For a non-minimum phase system, the proposed control design is a cascade system, where first controlled the inductor current and then the output voltage. This cascade configuration guarantees the correct power management for the different maneuvers by the UAV. The simulations show that it is possible to integrate a hybrid power generation system into the UAV.